THE RELATIONSHIP BETWEEN RELIGION AND REASON IN QURANIC STUDIES: INSIGHTS FROM CONTEMPORARY ISLAMIC PHILOSOPHY - Mahbub Setiawan; Abd. Hafid; Fuad Nawawi; Asep Abdurrohman; Suhirman; Mukhyar (LP2M Universitas PTIQ Jakarta, 2022)
Islamic Philosophy is a complex and multifaceted discipline that has undergone significant evolution over the centuries. In recent years, there has been a growing interest in the study of Contemporary Islamic Philosophy, reflecting the need to engage with the challenges facing Muslim communities in the modern world. This paper aims to provide a critical overview of the current trends in Contemporary Islamic Philosophy, focusing on key debates, developments, and applications of the discipline. The paper is based on a review of the literature in the field, and will provide insights into the ways in which contemporary scholars are reinterpreting classical Islamic thought and adapting it to the present-day context. The paper will also explore the relationship between Contemporary Islamic Philosophy and other related fields, such as Islamic studies, philosophy, religious studies, and social sciences